Surgical Technique of Late Spontaneous IOL-Capsular Bag Complex Dislocation with Low Corneal Endothelial Cell Density: A Case Report - Firman Setya Wardhana; Dhimas Hari Sakti; Supanji Supanji; Muhammad Bayu Sasongko; Tri Wahyu Widayanti; Angela Nurini Agni (International Journal of Retina, 2019)
Introduction: IOL-capsular bag complex dislocation is a rare but serious complication of phacoemulsification surgery. Technique to repair this complication should be based on various clinical parameters including quality of corneal endothelial cells and the type of dislocated IOL. Case Presentation: We present a case of a 67-year-old male with left eye spontaneous one-piece foldable IOL-capsular bag complex dislocation to vitreous cavity 4 years after phacoemulsification surgery. Visual acuity of the left eye was 1/60, pupil was round with 3 mm diameter and IOP was 15 mmHg. Noncontact specular microscopy examination showed that the corneal endothelial cell density was 1100 cells/mm2. It was managed with 23-gauge posterior vitrectomy, IOL evacuation to anterior chamber, releasing the capsular bag and repositioning the IOL into posterior chamber by sutured scleral fixation. Result: Follow-up at 6thmonth, best corrected visual acuity of the left eye achieved 6/6, IOL at central position and the last corneal endothelial cell density was 1076 cells/mm2. Conclusions: Late spontaneous IOL-capsular bag complex dislocation with low corneal endothelial cell density can be safely managed with proper surgical technique. Vitrectomy and sutured scleral fixation of the previously dislocated IOL were effective in managing such case. Longer follow-up should be done to assure the stability of IOL position and the quality of corneal endothelial cells.